HUBUNGAN ANTARA PERAN KADER JUMANTIK DENGAN UPAYA 3M PLUS KELUARGA DALAM PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) - Sofi Yulianto; Luluk Fauziyah Januarti (NHM PRESS, 2022)
Dengue fever disease is a disease that is caused by the dengue virus through mosquitoes. This disease is related with the environment condition and society behavior. Until now, tackling of DBD is still in preventing to exterminate of mosquito larva by 3M plus. Based on the study that is gotten by the researcher still less a maximum of 3M plus by family in Karang Dalem Village. One of the factors that influence the effort of 3M plus family in preventing DBD is the role of Jumantik cadre. This research has purpose to analyze the correlation between role of Jumantik cadre with the effort of 3M plus family in preventing DBD in Karang Dalem Village. The research design uses analytic by Cross Sectional approach. The population are 1941 familys and the sample are 194 familys in Karang Dalem Village. The technique sampling uses Proportional Random Sampling. The independent variable is the role of Jumantik cadre. The dependent variable is the effort of 3M plus family in preventing DBD. The instrumen of this research is questionnaire. The data is analyzed by using Spearman Rank statistic test. The result of the research from 194 familys in Karang Dalem Village. Based on the result of crosswise tabulation known that most of the role of Jumantik cadre is less with 3M plus family in preventing DBD. 115 familys is less in 3M plus and the result that is gotten from statistic test show that there is correlatios between the role of Jumantik cadre with the effort of 3M plus family in preventing DBD in Karang Dalem Village. Puskesmas needs to look for jumantik cadre besides works of civil servant with cadre who does not expect at earnings and cadre who is happy to assist in jumantik activity while effort of 3M plus less mothers who need more attention to action 3M plus